How minimum parking requirements make housing more expensive - Lewis Lehe (Journal of Transport and Land Use)
A growing consensus argues that minimum parking requirements (MPRs) make housing more expensive. This paper examines two claims from this discussion: (1) that MPRs discourage the construction of small units; (2) that the costs of building required parking are "passed on" to buyers and renters in the form of higher prices and rents. However, the mechanisms behind these two effects have never been made explicit in the literature. This paper proposes, for each claim, a plausible mechanism relying on the specific choices of housing suppliers and consumers. We propose that MPRs discourage small units because they eliminate the most profitable floorspace/parking bundle to supply to relatively lower-income households. We propose that parking costs may be passed on by reducing the supply of housing on offer at a given price.